Exploratory outcomes of the use of insulin degludec in the real world: data from the Association of British Clinical Diabetologists nationwide degludec audit - Steve Bain (British Journal of Diabetes, 2024)
Insulin degludec is a long-acting basal insulin analog that is used as a single daily injection in people living with type 2 diabetes (T2DM) or in combination with rapid-acting analogs in basal-bolus regimens in people living with T2DM or type 1 diabetes (T1DM). Registration studies showed benefits of reduction of hypoglycaemia rate and severity compared to previously available long-acting insulins.The Association of British Clinical Diabetologists nationwide clinical audit of insulin degludec is a real-world data program which includes a secondary care prospective data collection and a primary care retrospective data collection. Data were used to investigate the effects of degludec initiation in people living with T1DM or T2DM on hypoglycaemia rate and severity, change in haemoglobin A1c (HbA1c) and weight change.From the secondary care prospective and the primary care retrospective data 432 (of whom T1DM=273) and 3,513 (of whom T1DM=2,040) patients, respectively, were included in the analysis. HbA1c change was non-significant in people with T1DM and T2DM who were switched to insulin degludec due to hypoglycaemia in the secondary care cohort. A significant reduction of 3 and 10 mmol/mol was observed in people with T1DM and T2DM, respectively, when the switch to degludec was prompted by reasons other than hypoglycaemia, and in people with T1DM this was also associated with a 2.5 kg weight gain. There was a clinically significant reduction in minor, severe and nocturnal hypoglycaemia in 62%, 45% and 54% of T1DM and in minor hypoglycaemia in 44% of T2DM in the prospective cohort.Insulin degludec reduced HbA1c in people with diabetes who were started for non-hypoglycaemia reasons and in people in the retrospective cohort. The extent of reduction in HbA1c was similar in both cohorts, even after stratification for T1DM and T2DM. Overall, insulin degludec resulted in lower HbA1c and modest weight gain in people starting for non- hypoglycaemia reasons and lower hypoglycaemia without any change in HbA1c or weight in people switching due to hypoglycaemia.